Analisis Learning Loss Pada Anak Usia Dini di Gugus V Buleleng - Indah Cahayani Damanik; I Wayan Widiana; Putu Rahayu Ujianti (Universitas Pendidikan Ganesha, 2023)
Learning loss or loss of knowledge is a condition where children lose achievements and skills in academic development due to the cessation of learning in education. Currently, learning loss often occurs in early childhood. This research is analytical with data collection methods through interviews, observation, and documentation. This research method is descriptive and qualitative, using primary data from sources. Data analysis techniques in this research using data collection analysis, data reduction, data presentation, and verification show that several factors cause students to experience learning loss. The research results found that the teacher's role divides the learning process into two major stages, namely apperception and the strategy or method used. It states that the perception carried out by the teacher before learning has a significant influence on overall learning. Next to stage two, namely the method used. Children or early childhood students experience learning loss in the early or odd semesters due to the change in learning activities from online to offline, often called blended learning. The difficulties experienced by teachers when facing learning loss are the need for more learning media for children, and to cover this shortage, teachers exchange media and get closer to children whose development needs to catch up. Children or early childhood students experience learning loss in the early or odd semesters due to the change in learning activities from online to offline, often called blended learning. The difficulties experienced by teachers when facing learning loss are the need for more learning media for children, and to cover this shortage, teachers exchange media and get closer to children whose development needs to catch up. Children or early childhood students experience learning loss in the early or odd semesters due to the change in learning activities from online to offline, often called blended learning. The difficulties experienced by teachers when facing learning loss are the need for more learning media for children, and to cover this shortage, teachers exchange media and get closer to children whose development needs to catch up.